The Effect of Liquidity, Growth Opportunity, and Financial Distress on Hedging Decisions - Pratomo, Ilfat; Hasanah, Nuramalia; Armeliza, Diah (LPPM Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of liquidity, growth opportunity, and financial distress on hedging decisions in manufacturing companies listed on the Indonesia Stock Exchange. The sample selection technique used was a purposive sampling technique which consisted of 320 observations during 2016 – 2020. The data used is secondary data derived from company financial reports obtained from the Indonesia Stock Exchange (IDX) website and several other sources. The data analysis technique used in this study is logistic regression analysis using the Statistical Product and Service Solution (SPSS) version 26 application. The results of this study indicate that liquidity has an influence on hedging decisions, growth opportunity has no effect on hedging decisions, and financial distress has an influence on hedging decisions.